(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
The goal of this study was to detect the degree of applying distance learning management among school principals in the Governorate of Jerash from the perspectives of school principals and teachers. The study sample, which was selected using the stratified random method, consisted of (354) individuals: (142) principals and (212) teachers. A descriptive survey approach was employed in the study. To achieve the goals of the study, a questionnaire was designed, which invlved four fields. The most important results of the study showed that the degree of applying distance learning management among school principals in the Governorate of Jerash from the perspective of school principals and teachers was moderate. The results also indicated that there were statistically significant differences at (α=0.05) in the estimates of the study sample of the degree of application of distance learning management among school principals which are ascribed to the academic qualification) variable, in favor of graduate studies, to the job title variable, in favor to teachers. In addition, the results showed that there were no statistically significant differences due to the variables of gender and years of experience.